Increasing Lecturer Innovation through Strengthening Personality, Transformational Leadership, Organizational Culture and Work Motivation Using Path Analysis and SITOREM Analysis Techniques at Politeknik Negeri Jakarta - Susanti, Eni; Rubini, Bibin; Setyaningsih, Sri (Indonesian Journal of Education and Mathematical Science, 2024)
This study aims to find out empirical data and find strategies and ways to increase lecturer innovation through efforts to strengthen personality, transformational leadership, organizational culture and work motivation. This study uses the path analysis method that is used to determine the direct and indirect effect between variables, then followed by SITOREM analysis to analyze the indicators of research variables so that efforts will be made to increase lecturer innovation through strengthening personality, leadership transformational, organizational culture and work motivation. The population of this study was a lecturer at the Jakarta State Polytechnic, totaling 398 lecturers with a number of research samples of 200 lecturers taken with random sampling techniques using the Slovin formula. The results of the path analysis shows that there is a significant positive direct effect of personality (X1) on lecturer innovation (Y) with βy1 = 0.205, there is a significant positive direct effect of transformational leadership (X2) on lecturer innovation (Y) with βy2 = 0.245, there is a significant positive direct of organizational culture (X3) on lecturer innovation (Y) with βy3 = 0.211, there is a significant positive direct effect of work motivation (X4) on lecturer innovation (Y) with βy4 = 0.344. There is a significant positive direct of personality (X1) on work motivation (X4) with βy41 = 0.239, there is a significant positive direct of transformational leadership (X2) on work motivation (X4) with βy42 = 0.301, there is a significant positive direct effect of organizational culture ( X3) on work motivation (X4) with βy43 = 0.394. There is a significant positive indirect effect of personality (X1) on lecturer innovation (Y) through work motivation (X4) with βxy1 = 0.049, there is a significant positive indirect effect of transformational leadership (X2) on lecturer innovation (Y) through work motivation (X4) With βxy2 = 0.074, there is a significant positive indirect effect of organizational culture (X3) on lecturer innovation (Y) through work motivation (X4) with βxy3 = 0.083. And based on the SITOREM analysis, several efforts were made to increase lecturer innovation by improving indicators, are: 1) product development; 2) use of new models; 3) product improvement; 4) products produced; 5) communication with customers; 6) model improvement and 7) relationships with customers. Efforts to strengthen personality by improving indicators, are: 1) openness; 2) awareness; and 3) neuroticism, and maintaining or developing good indicators, are: 1) agreeableness and 2) extraversion. Efforts to strengthen transformational leadership by improving indicators, are: 1) exemplary; 2) inspiration; and 3) innovative behavior; and maintaining or developing good indicators, are: 1) creation; 2) trusted behavior; and 3) loyalty. Efforts to strengthen organizational culture by maintaining or developing good indicators, are: 1) the atmosphere felt by members in the life of the organization, 2) the most important (dominant) values that members, 4) patterns of organizational behavior, and 5) norms and standards of behavior at work; And efforts to strengthen work motivation by improving indicators, are: 1) achievement; 2) meeting affiliate needs; 3) work completion; and 4) participation, and maintaining or developing good indicators, namely; 1) morale; 2) opportunities and 3) utilization of expertise.